Geometric Tracking Control of a Quadrotor on SE(3) using left tracking error function. (2020) - Sharma, Manmohan; Kar, Indrani
Abstract: This paper presents geometric tracking control law for a quadrotor UAV on SE(3) using left tracking error function as compared to right tracking error function reported in the literature. The use of left tracking error function results in a simpler control law design as compared to right tracking error function. The configuration errors have been defined on SE(3) using geometric approach. Rigorous mathematical proof have been given to show the exponential stability of the closed loop system under positive definiteness conditions on some matrices. Simulation results have been presented using this simpler control law to validate the designed control law.